An Effective Approach to Contention Based Bandwidth Request Mechanism in WiMAX Networks (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2012)
In this paper the IEEE 802.16 standard based Mobile WiMAX (Worldwide Interoperability for Microwave Access) system is investigated for the purpose of Quality of Service provisioning. As a potential solution, scheduling algorithms have been taken into major concern. Within the pool of scheduling algorithms and for the purpose Contention based bandwidth request resolution, the Modified Contention Based BW Resolution algorithm (MCB-BWR-Scheme) is proposed. Supported by the fact that the standard does not emphasize a specific scheduling algorithm for contention period based services, therefore, the choice of the scheduling algorithm for the WiMAX systems is very important. There are several scheduling algorithms for WiMAX in the literature, however, studies show that an efficient, fair and robust scheduling algorithm for WiMAX systems is still an open research area and hence a well thought out algorithm will be of great contribution to the area under investigation. Results from the OPNET Modeler simulation program show that the adjusted algorithm works well with delay and throughput constraints. It is also in consistent with the quality of service demands of the video and voice traffic.